Disentangling vibronic and solvent broadening effects in the absorption spectra of coumarin derivatives for dye sensitized solar cells1. Issue 17 (7th May 2015) - Cerezo, Javier; Avila Ferrer, Francisco J.; Santoro, Fabrizio
<x xml:space="preserve">Abstract</x> Individuation of vibronic and solvent contributions to the spectra of a family of coumarin dyes helps to understand the main differences in their lineshapes.